Accurate frequency estimation from faulty power systems - Low, Poo Chuan (2018)
The aim of the research is to develop an algorithm which able to compute accurate frequency estimation in faulty power system. A general equation which represent the simplified version of 3-phase power system is developed and provided the waveform analysis. The project has been carried out in MATLAB environment for stimulation purpose. The project is achieved through the use of Clarke’s Transformation in order to provide a transformed waveform from 3-phase to 2 reference axes. Park’s Transformation is then implemented into the project to transform the waveform from time domain into rotating reference domain. Quaternion and complex knowledge has been integrated into the system for 3-dimensional graph view. Last but not least, the waveforms have been processed using Fast Fourier Transform to obtain the waveform components for analysis purpose. The final MATLAB algorithm is validated across various type of synthetic fault only.